Workers in informal employment organising and acting collectively: The role of trade unions - Edlira Xhafa; Melisa R. Serrano (Global Labour University - Freunde und Förderer e.V., 2024)
The expansion of informal employment has been associated with increased exploitation and decent work deficits, leading to widespread poverty and growing inequalities. In response, a variety of forms of collective representation and action by and with informal workers have emerged demanding better and more stable incomes, job stability, better working conditions, access to social protection and protection from discrimination and harassment. In many cases, these workers are joining existing unions or forming new ones to press for their demands within the existing institutions of collective bargaining. In some other cases, the forms of worker representation bear many similarities to the early days of the labour movement as do their demands, which often go beyond immediate workplace needs and are framed in broader, more political terms. In particular, some groups of informal workers are pushing for a transformation of collective bargaining, both in terms of involving more actors and broadening the bargaining agenda. Contrary to the perception that unions have been lax in responding to the new challenges posed by the rise of informal employment, the literature suggests a process of union transformation that may be more advanced than it is generally acknowledged in academic debates. Rather than rendering unions obsolete, the diversity of forms of collective representation and action by workers in informal employment is reshaping unions, potentially strengthening them, or pushing them to rediscover their historical social movement identity. The research suggests that the future of worker representation is a bricolage of more inclusive forms of organisation, underpinned by more grassroots mobilisation and action, with the effect of revitalising the labour movement.
Keywords: 330; workers informal employment